Effect of ultramarathon running on iron metabolism. Issue 1 (4th October 2022) - Li, Li-Hua; Hou, Sen-Kuang; Chen, Chung-Ting; Chang, Yuan-I; Kao, Wei-Fong; Chiu, Yu-Hui; Juan, Chi-Chang; How, Chorng-Kuang
Abstract : Background: Iron is a vital trace element for energy production and oxygen transportation; importantly, it is essential to athletic performance. Maintaining iron balance is tightly controlled at systemic and cellular levels. This study aimed to determine serum iron tests, hepcidin levels, and cellular iron import and export activities in peripheral blood mononuclear cells (PBMCs) in ultramarathon runners to elucidate the association of systemic inflammation response and iron metabolism. Methods: Sixteen amateur runners were enrolled. Blood samples were taken 1 week before, immediately, and 24 h after the run. Plasma hepcidin levels were measured by enzyme-linked immunosorbent assay. The expression levels of divalent metal iron transporter 1 (DMT1), ZRT/IRT-like protein 14 (ZIP14), transferrin receptor 1 (TfR1), and ferroportin (FPN) in PBMCs were measured using real-time quantitative reverse transcription-polymerase chain reaction. Results: Serum iron concentrations and transferrin saturation significantly decreased immediately after the race and dramatically recovered 24 h post-race. Serum ferritin levels had a statistically significant rise immediately after the race and remained high 24 h after the completion of the race. Ultramarathons were associated with increased plasma interleukin-6 concentrations corresponding to the state of severe systemic inflammation and therefore boosted plasma hepcidin levels. The expression levels of DMT1 and FPN mRNA were markedly decreased immediately and 24 h after the race. The ZIP14 and TfR1 mRNA expression in PBMCs significantly decreased immediately after the race and returned to the baseline level at 24 h post-race. Positive significant correlations were observed between plasma hepcidin and ferritin levels. Conclusion: Iron homeostasis and systemic inflammatory response are closely interconnected. Cellular iron import and export mRNA activities in PBMCs were acutely inhibited during an ultramarathon.